Combining higher-load and lower-load resistance training exercises: A systematic review and meta-analysis of findings from complex training studies - Bauer, P.; Uebellacker, F.; Mitter, B.; Aigner, A. J; Hasenoehrl, T.; Ristl, R.; Tschan, H.; Seitz, L. B. (Journal of Science and Medicine in Sport, 2019)
Objectives: The aim of the present meta-analytical review was to determine the effectiveness of training programmes combining higher-load and lower-load exercises in one workout (i.e. complex training [CT]) on lower-body performance. Design: Systematic review and meta-analysis. Methods: A search of five electronic databases (PubMed, Web of Science, SportDiscus, CINAHL and Scopus) was conducted to identify all publications up to 7 March 2018. Meta-analyses were performed using a random-effects model with the dependent variables countermovement jump (CMJ) height, squat jump (SJ) height, one-repetition maximum (1-RM) squat performance and sprint time for 5 m, 10 m, 20 m, 30 m and 40 m, respectively. Results: The analysis comprised 33 studies and a total of 1064 healthy participants. The meta-analysis revealed that CT is effective in improving CMJ (95% confidence interval [CI] 5.6%-12.3%), SJ (95% CI 8.0%-17.4%), 1-RM squat (95% CI 16.4%-30.7%) and sprint performance (5 m = 95% CI -14.8% to -0.9%, 10 m = 95% CI -6.0% to -2.1%, 20 m = 95% CI -7.4% to -1.4%, 30 m = 95% CI -8.0% to -0.6%). However, when directly compared to traditional training methods, only 1-RM squat strength performance and 20 m sprint time were superior following CT interventions (95% CI 0.2%-13.7% and 95% CI -1.6% to -0.1%, respectively) Conclusions: CT is an acceptable method for improving jump, strength and sprint performance in athletes. Compared to traditional training methods, CT seems to produce superior training effects only for 1-RM squat and 20 m sprint performance; however, these findings were influenced by single studies and should be therefore interpreted with circumspection.